2011
DOI: 10.1007/s11627-011-9347-6
|View full text |Cite
|
Sign up to set email alerts
|

In vitro propagation from young and mature explants of thyme (Thymus vulgaris and T. longicaulis) resulting in genetically stable shoots

Abstract: An efficient in vitro propagation protocol, applicable both to young and mature explants of two Thymus spp., results in genetically stable plantlets. In vitro-grown shoot tips of Thymus vulgaris L. were exposed to cytokinins (6-benzyladenine, kinetin, and thidiazuron) alone or in combination with auxins, gibberellic acid (GA 3 ) and/or silver nitrate in order to optimize in vitro shoot proliferation. Optimum shoot proliferation (97% regeneration rate, with 8.6 shoots produced per explant) was obtained when sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
56
2
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 33 publications
7
56
2
1
Order By: Relevance
“…This result are in agreement with Peyvandi et al (2013) who reported all of the mentioned fragments were monomorphic, confirming the genetic stability of the micropropagated plants of Olea europaea. Also agree with Ozudogru et al (2011) who reported all of bands were monomorphic through 10 subculture of Thymus vulgaris and T. longicaulis. In opposite of, ISSR markers showed high polymorphic bands especially in subcultures 7, 8 and 9.…”
Section: Effect Of Subculture On Genetic Stabilitysupporting
confidence: 88%
See 1 more Smart Citation
“…This result are in agreement with Peyvandi et al (2013) who reported all of the mentioned fragments were monomorphic, confirming the genetic stability of the micropropagated plants of Olea europaea. Also agree with Ozudogru et al (2011) who reported all of bands were monomorphic through 10 subculture of Thymus vulgaris and T. longicaulis. In opposite of, ISSR markers showed high polymorphic bands especially in subcultures 7, 8 and 9.…”
Section: Effect Of Subculture On Genetic Stabilitysupporting
confidence: 88%
“…RAPD markers have been used successfully to assess genetic stability among somatic embryos in spruce species (Isabel et al, 1993;. Panda et al (2007) evaluated the genetic stability of micropropagated clones of Curcuma longa L. over 26 months in culture by random amplified polymorphic DNA (RAPD) analysis, Also Genetic stability of thyme was confirmed in the in vitro-germinated mother plant as well as the shoots that underwent two, four, six, eight and ten cycles of in vitro subculturing by RAPD analysis (Ozudogru et al, 2011). The ISSR markers have also been used successfully to assess genetic stability among micropropagated plants (Joshi and Dhawan, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The essential oils produced by Thymus spp. are important for the cosmetic industry, and due to their antiseptic, antispasmodic and antimicrobial properties, they are also used for medicinal purposes (Cosentino et al 1999;Figueiredo et al 2001;Stahl-Biskup and Saéz 2002;Ozudogru et al 2011). The chemical composition and the antimicrobial activity of T. lotocephalus essential oils have already been reported (Salgueiro et al 2000;Figueiredo et al 2001;Faleiro et al 2003).…”
Section: Introductionmentioning
confidence: 97%
“…Certain types of callus cultures give rise to clones that have inheritable characteristics different from those of parent plants due to the occurrence of somaclonal variability (George 1993), which can lead to the development of commercially important improved varieties (Lee and Chen 2014). IVP protocols have already been established for Thymus species, such as T. vulgaris and T. longicaulis (Ozudogru et al 2011), and T. lotocephalus (Coelho et al 2012). Recently, micropropagation of T. persicus via direct organogenesis has been reported from our laboratory (Bakhtiar et al 2014).…”
Section: Introductionmentioning
confidence: 99%